A Methodological Study on Expanding the Microarchitectural Design Space of Melt Electrowriting - Kai Cao; Yi He; Anni Wang; Yunpeng Wang; Junyi Song; Jun Zhong; Qisheng Chen; Rongwu Wang (Engineering Reports)
ABSTRACT Melt electrowriting (MEW), an advanced additive manufacturing technique for fabricating microfibers, has demonstrated significant potential in tissue engineering applications. While MEW shares many similarities with fused filament fabrication (FFF), the conventional slice‐filling algorithms used in FFF are ill‐suited for MEW, as they fail to address the requirements for continuous toolpaths and diverse microarchitectures. While previous studies have proposed various micropatterns for specific applications, a systematic methodology for microarchitectural design is still lacking, limiting MEW's capabilities. To address this gap, three methods are proposed herein, with their unique role in diversifying the design of micropatterns. Method 1 allows the generation of continuous patterns with homogeneous microarchitectures through replication, rotation, and superimposition of one or two primary structural units. Method 2 enables the replacement of primary structural units within a continuous pattern, allowing local deformation of the microarchitecture. Method 3 applies a global deformation on the original pattern with a matrix. These methods, when used individually or in combination, can significantly expand the microarchitectural design space, thereby enhancing the versatility and application scope of MEW in tissue engineering.